Methodological Problems of Labor Market Evaluation in the Digital Economy - Abdumalik Ortigalievich, Ruziev; Mahsud Mardon Ogli, Mahammadiev (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses the behavior of employers and workers in terms of the use of information and communication technologies in labor and economic processes in the context of the development of the digital economy and discusses methodological issues of analysis and evaluation of labor market performance as a result of this behavior. Trends in the use of digital technologies in economic life, employment relations, and the impact of digital platforms on the development of education have been studied. In the context of globalization of the economy on a global scale, the main directions and institutional procedures for effective regulation of the labor market have been identified.